Happiness as a Predictor of Psychological Well-Being of Male Athlete Students - Abdollah Ghasempour; Heidar Jodat; Masomeh Soleimani; Kiomars Zhalehshabanlo (The Society of Aging and Physical Activity (SAPA), 2013)
Happiness is a concept which has become of high importance for the past years because of its role in psychological well-being and the social health of people. The present research has been conducted to study the role of happiness in predicting the psychological well-being of male athlete students. A number of 100 physically active students were chosen through multistep cluster sampling out of male physically active students in the city of Miyandoab in the academic year 1391-92. They responded to the short scale depression-happiness of Joseph et al. (with the stability of 0.69) and Ryff's scale of psychological well-being (with the stability of 0.68) having six components of self-acceptance, environmental mastery, positive relations with others, purpose in life, personal growth and independence. The results showed that there is a relationship between happiness and well-being (r = 0.53). Also, happiness, in a positive and meaningful way, predicts changes pertaining to psychological well-being (p < 0.001; r2 = 0.282). Enhancing and improving happiness along with physical and sportive activities may help increase psychological well-being of students.